Monitoring and control process for composting sewage sludge through respirometric method - Scoton, E. J. [UNESP]; Battistelle, R. A.G. [UNESP]; Renófio, A. [UNESP]; Akutsu, J. [UNESP]; Cavenaghi, V. [UNESP]; Egea, J. S. [UNESP] (My University, 2013)
Composting is an important tool for the treatment of the organic fraction of solid waste through the use of technologies that process the waste generated from agriculture, agribusiness, forestry, households, and also sludge from sewage treatment plant, adapting them to be incorporated into the soil and contributing to reduction of chemical fertilizers. This study evaluates the use of an automated respirometer with hermetic rotary reactor to evaluate the parameters of O2 and CO2 during the co-composting of sewage sludge and grass clippings. The traditional composting process is highly empirical in terms of its control and evaluation of the process, which consists of daily temperature readings. In the respirometric method, the parameters of degradation are measured in the gas phase of the composting process, obtaining data lines 1440/day, with the advantage of greater representativeness, accuracy and reliability.
Keywords: Composting; Respirometric method; Sewage sludge; Solid waste